2011
DOI: 10.1039/c1cc14694g
|View full text |Cite
|
Sign up to set email alerts
|

Iron-catalyzed oxidative coupling of arylboronic acids with benzene derivatives through homolytic aromatic substitution

Abstract: Fe(OTf)(3)-1,10-phenanthroline catalyzes oxidative coupling of arylboronic acids with benzene derivatives using t-BuOOt-Bu as an oxidant. The reaction proceeds through homolytic aromatic substitution with aryl radicals generated from arylboronic acids and t-BuO˙.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Nakamura and co-workers contributed significantly to the development of iron-catalyzed C-C bond-forming reactions by using boronic ester derivatives with halogenated compounds. [12] The Hayashi group reported the Fe(OTf) 3 -catalyzed oxidative coupling of unreactive benzene with boronic acids, [13] and Li and co-workers reported the ligand-free iron-catalyzed arylation of benzoazole with aldehydes in the presence of O 2 as the oxidant. [11] Also, the synthesis of Het-Ar and Quin-Ar compounds by using a stoichiometric amount of an iron source (i.e., FeS) was recently reported by the same group.…”
Section: Introductionmentioning
confidence: 99%
“…Nakamura and co-workers contributed significantly to the development of iron-catalyzed C-C bond-forming reactions by using boronic ester derivatives with halogenated compounds. [12] The Hayashi group reported the Fe(OTf) 3 -catalyzed oxidative coupling of unreactive benzene with boronic acids, [13] and Li and co-workers reported the ligand-free iron-catalyzed arylation of benzoazole with aldehydes in the presence of O 2 as the oxidant. [11] Also, the synthesis of Het-Ar and Quin-Ar compounds by using a stoichiometric amount of an iron source (i.e., FeS) was recently reported by the same group.…”
Section: Introductionmentioning
confidence: 99%
“…It is fascinating to note that iron grafted 2 wt %Fe/AlSBA‐15 catalyst with lowest iron content performed with 52 % biphenyl yield which is higher than yield obtained with the Fe/SBA‐15 catalyst having maximal iron content of 8 wt %. Further increase of iron loading in Fe/AlSBA‐15 catalyst significantly improved the biphenyl yield up to 82 % and the obtained isolated yield of 74 % is equal to the yield obtained with the homogeneous iron catalyst in the presence of additives . The effect of electron withdrawing groups attached to the homogeneous iron catalyst and addition of substituted 1,10‐phenanthroline on enhancing coupled product yield has to be taken into account to understand the role of grafted alumina in 8 wt %Fe/AlSBA‐15 as a solid‐state ligand to boost biphenyl yield through its Lewis acid nature …”
Section: Resultsmentioning
confidence: 99%
“…With the aim of designing an effective heterogeneous iron catalyst for C−C coupling reaction, in our recent report, by implementing the SED technique 8 wt % of iron was successfully grafted as isolated, cluster and oligomeric oxidic iron species over the high surface area mesoporous silica support (SBA‐15) without forming the bulk iron oxide . The 8 wt %Fe/SBA‐15 was employed as redox catalyst for activation of C( sp 3 )‐H and C( sp 2 )‐H reactions like arylation of biphenyl methane and benzene, respectively. The catalyst demonstrated excellent activity like the homogenous iron salt (FeCl 2 ) in case of arylation of biphenyl methane.…”
Section: Introductionmentioning
confidence: 99%
“…(t-BuO) 2 mixture for the oxidative coupling of boronic acids with arenes. [89] Demir et al, who had reported the MnA C H T U N G T R E N N U N G (III)-mediated radical arylation of heteroarenes with arylhydrazines in 2002, [81] extended their methodology to arylboronic acids as radical source, using the optimized conditions previously reported.…”
Section: Arylboronic Acidsmentioning
confidence: 97%
“…Later on, the combination of an organic oxidant with a catalytic amount of transition metal has been used for the radical arylation of quinones [85c,87] and biaryls. [88,89] For instance, Baran et al developed a new synthesis of fluorenones through intramolecular radical cyclisation, using 0.2 equivalent of AgNO 3 and 3 equivalents of K 2 S 2 O 8 as radical initiators, [88] whereas Shirakawa and Hayashi rather used a 10 mol% FeA C H T U N G T R E N N U N G (III)/10 mol% phenanthroline/2 equiv. (t-BuO) 2 mixture for the oxidative coupling of boronic acids with arenes.…”
Section: Arylboronic Acidsmentioning
confidence: 99%